2004
DOI: 10.12702/1984-7033.v04n03a13
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic index in Myrtaceae native fruits trees from southern Brazil

Abstract: -This work aimed to evaluate meiotic index in Myrtaceae species

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…3). This result was higher than that observed by Franzon & Raseira (2004), who obtained values of 35.3% and 33.5%, respectively, in two accessions of Surinam cherry. The results obtained in this study are also higher than those obtained by Franzon et al (2007), who analyzed the in vitro germination capacity of Surinam cherry pollen using various types of culture and obtained germination results below 30%.…”
Section: Resultscontrasting
confidence: 77%
See 1 more Smart Citation
“…3). This result was higher than that observed by Franzon & Raseira (2004), who obtained values of 35.3% and 33.5%, respectively, in two accessions of Surinam cherry. The results obtained in this study are also higher than those obtained by Franzon et al (2007), who analyzed the in vitro germination capacity of Surinam cherry pollen using various types of culture and obtained germination results below 30%.…”
Section: Resultscontrasting
confidence: 77%
“…Several types of molecular markers have been used for the analysis of genetic diversity in different species, but there are few records for native species of the South of Brazil (Franzon & Raseira 2004), mainly species of the Myrtaceae family; which may be associated with the presence of polyphenols that hinder DNA extraction (Almeida et al 2012). In this study, RAPD markers were used because it is a simple, fast, and relatively inexpensive technique with informative potential, although it presents repeatability problems (Areias et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Costa and ForniMartins (2006a) evaluated the meiosis and pollen viability of four species of the Campomanesia and Psidum genus and did not observe any abnormalities and also identified a pollen viability higher than 86%. Franzon and Raseira (2004) observed cytological stability higher than 96% in Acca sellowiana, while in Eugenia pyriformis and Campomanesia xanthocarpa the stability was 89.5% and 89.3%, respectively.…”
Section: Guerra Et Almentioning
confidence: 80%
“…Franzon and Raseira (2004) and Franzon et al (2007) evaluated the germination capacity of cherry tree pollen and found values higher than 60%. These results may be associated with the methodology since, according to Marcellán and Camadro (1996), many factors can influence germination, such as: culture medium, incubation temperature and length.…”
Section: Guerra Et Almentioning
confidence: 99%